Effects of Stroke on Ipsilesional End-Effector Kinematics in a Multi-Step Activity of Daily Living - Gulde, Philipp; Hughes, Charmayne Mary Lee; Hermsdörfer, Joachim (Frontiers in Human Neuroscience, 2017)
Background: Stroke frequently impairs activities of daily living (ADL) and deteriorates the function of the contra- as well as the ipsilesional limbs. In order to analyze alterations of higher motor control unaffected by paresis or sensory loss, the kinematics of ipsilesional upper limb movements in patients with stroke has previously been analyzed during prehensile movements and simple tool use actions. By contrast, motion recording of multi-step ADL is rare and patient-control comparisons for movement kinematics are largely lacking. Especially in clinical research, objective quantification of complex externally valid tasks can improve the assessment of neurological impairments. Methods: In this preliminary study we employed three-dimensional motion recording and applied kinematic analysis in a multi-step ADL (tea-making). The trials were examined with respect to errors and sub-action structure, durations, path lengths, peak velocities, relative activity and smoothness. In order to check for specific burdens the sub-actions of the task were extracted and compared. To examine the feasibility of the approach, we determined the behavioral and kinematic metrics of the (ipsilesional) unimanual performance of 7 chronic stroke patients (64a±11a, 3 with right/4 with left brain damage, 2 with signs of apraxia, variable severity of paresis) and compared the results with data of 14 neurologically healthy age-matched control participants (70a±7a). Results: T-tests revealed that while the quantity and structure of sub-actions of the task were similar. The analysis of end-effector kinematics was able to detect clear group differences in the associated parameters. Specifically, trial duration was increased (Cohen’s d=1.77); the relative activity (Cohen’s d=1.72) and the parameters of peak velocities (Cohen’s d=1.49/1.97) were decreased in the patient group. Analysis of the task’s sub-actions (rmANOVA) revealed no impact of the different demands of the sub-actions on the relative performance of the patient group. Conclusion: The analyses revealed kinematic peculiarities in the performance with the ipsilesional hand. These deficits apparently arose from the cognitive demands like sequencing rather than motor constraints. End-effector kinematics proved as a sensitive method to detect and quantify aspects of disturbed multi-step ADL performance after stroke. If standardized, the examination and the analysis are quick and deliver objective data supporting clinical research.